FLORISTIC NOTES ON LICHENS IN THE FILDES PENINSULA OF KING GEORGE ISLAND AND HARMONY COVE OF NELSON ISLAND, SOUTH SHETLAND ISLANDS, THE ANTARCTIC (14th Symposium on Polar Biology) - イノウエ, マサカネ; INOUE, Masakane (National Institute of Polar Research, 1993)
P(論文) Floristic interests of lichens in the Fildes Peninsula of King George Island and Harmony Cove of Nelson Island belonging to the maritime Antarctic zone are mentioned. A total number of species occurring in the present region is discussed comparing it with the estimations of previous authors. Preliminary contributions to a phytogeography are mentioned. The lichens enumerated from the present region are classified into three major groups by their distribution patterns; 1) species known only from the maritime Antarctic, 2) species often reported from the maritime Antarctic, but hardly known from the continental Antarctic, and 3) species known to occur in the maritime and continental Antarctic. Concerning the distributions of four species not belonging to these major groups are briefly discussed. departmental bulletin paper